A Clinical Study of Surgical Treatment of Patients With Carcinoma of the Cervical Esophagus Extending to the Thoracic Esophagus - Saito, Reijiro; Suzuki, Hiroyuki; Motoyama, Satoru; Sasaki, Shin-ichi; Okuyama, Manabu; Ogawa, Jun-ichi; Kitamura, Michihiko (General thoracic and cardiovascular surgery, 2000)
We studied optimum surgery for carcinoma of the cervical esophagus extending to the thoracic esophagus (Ce-Ut carcinoma). Subjects were 13 patients diagnosed with Ce-Ut carcinoma treated at our institute from January 1989 to December 1998. Clinicopathologic information such as surgical procedures, pathologic findings, and postoperative complications were analyzed. In 10, laryngoesophagectomy was conducted due to tracheal invasion by the tumor. In 7, mediastinal tracheostomy was done because of the extended resection of the proximal trachea. In 3, the larynx was preserved and, in 2, cricopharyngeal myotomy was added. Lymph node metastasis was found only in the neck and the upper mediastinum at surgery and recurrences were all lung metastasis. The incidence of postoperative complications was very high (76.9%), and 1 patient died due to widespread tracheal necrosis. The cumulative 5-year survival rate for the group was 33.3% and that for the 9 curative cases was 50%, but most of the cases who underwent noncurative resection and/or who received preoperative therapy for widespread invasion to surrounding organs died within a year. The prognosis of patients who undergoing curative extended resection of the proximal trachea and suitable lymph node dissection in the neck and upper mediastinum may improve, and larynx-preserving surgery is recommended for patients without tracheal invasion. Despite preoperative chemoradiotherapy, the prognosis of patients with widespread invasion to surrounding organs was very poor, and clinical studies on new therapeutic strategies for these advanced cases are needed to improve the prognosis of Ce-Ut carcinoma patients.